Curating context : beyond the gallery and into other fields - Malm, Magdalena (Stockholm : Art and Theory Publishing, 2017)
Curating Context' describes a field where the curatorial practice is extended beyond curating exhibitions into working with entire contexts. It articulates the why and how of curating art projects that gain their meaning in relation to a surrounding context, or which need a specific structure in order to play out. In this practice, curatorial considerations are interwoven with the production, and the intentions of artists and curators lead the way rather than institutional structures. The texts and conversations in this book reflect on how these curatorial methodologies not only situate works in different places, but also transfer curatorial methods into other fields, such as the context of law, urban development, and constructions of the civic. This exciting curatorial approach where each project sets new demands, requires very specific skills rarely taught in curatorial programs. Curating Context is an attempt to share a sustained conversation among practitioners in the field.
Curating context : introduction / Magdalena Malm -- Survival guide for art production / Maria Mur Dean -- Curating inside the mind / Raimundus Malašauskas / Magdalena Malm -- The play of protagonists / Raqs Media Collective -- How about this? : on a sense of togetherness / Elvira Dyangani Ose / Magdalena Malm -- Projects -- From crystal ball gazing to air traffick control / arts producing in public contexts / Claire Doherty -- Perceptions of care / Nato Thompson / Suzanne Lacy -- Curating infrastructure / Joanna Zawieja / Jessica Segerlund -- Transforming, composing, instituting, disappearing : four movements of the curatorial inquiry / Grégory Castéra.
Translated from Swedish.
Produced in collaboration with the Public Art Agency Sweden.
boek